Contextual Model on Clinical Hypnotherapy for a Client with Chronic Schizophrenia in Hong Kong - ying , Hiu; keung, Man (International Journal of Psychosocial Rehabilitation, 2018)
BackgroundEvidence of clinical studies affirmed the impact of hypnotherapy by reducing pain and anxiety, and enhancing relaxation. The efficacy of hypnotherapy in stress reduction and pain control for persons with mental illness was evaluated through a conceptual framework of Contextual Model.MethodThe subject recruited from the community was invited to participate in five treatment sessions in a consecutive of three months. Each session lasted for 60-90 minutes. Pre-talk, hypnotic induction, deepening, post-hypnotic suggestion and debriefing would be carried out as systematized intervention. Client’s level of hope, mental well-being and intensity of pain would be assessed by standardized assessment tools.ResultsResults indicated improvement in Chinese Hope Scale with total score increased from 44 to 56; the score of Chinese Short Warwick-Edinburg Mental Well-being Scale rose from 20 to 28; the pain score recorded from the initial interview was 6/10, and thereafter decreased to 1/10 upon completion of session three.ConclusionHypnotherapy enhances psychological well-being with positive effects of stress reduction and pain relief.